Landscapes or seascapes? - Thoen, Erik; Borger, Guus J.; de Kraker, Adriaan M. J.; Soens, Tim; Tys, Dries; Vervaet, Lies; Weerts, Henk J.T. (Brepols, 2013)
This volume deals with the geographical evolution of the coastal areas adjacent to the North Sea, with a focus upon the last two thousand years. Although many articles are reworked in a fundamental way, most of them are the result of a conference which took place in 2010 at Ghent University (Belgium) and which was actually the third in a series of symposiums on the same broad theme. The first took place in 1958, and the second in 1978. Recognized specialists were invited to present their research in a variety of fields relating to the subject. The various disciplines in which the coastal plains are studied too often remain within their own borders, and so we have set out to thoroughly interweave them in the hope that this will spur greater interdisciplinary cooperation. This collection of texts is intended to appeal not just to experts in historical geography, but to historians and scientists working in any field who wish to gain insights into the present ‘state of play’. Detailed geological research about many areas provided new data and researchers gradually gained a better understanding of the close relationship between the processes of deposition, sea-level change, and land formation taking place across multiple regions. In the same time, historical and archaeological research also evolved. Most significantly, ideas regarding the chronology of human occupation have changed a lot. This scope of the research collected in this volume is important because it has increasingly become evident that land loss and gain were the results of regional factors, including and especially human activities. Moreover, it is now clear that humans devised survival strategies, and thus organized their activities in relation to the environment, on a regional basis, which means that the causes of local changes must have been both natural and socio-historical. It has now become clearer than ever that there is no single chronological scheme capable of explaining the coastal evolution across the entirety of the North Sea area. <span class=